Strategic Planning and Institutional Excellence in Lake Chad Research Institute: A Beginner’s Guide to Understanding Pathways - Kirfi, Musa Mohammed; Aliyu, Almustapha A.; Solomon, Othniel; Bature, Abubakar Dahiru (Kashere Journal of Politics and International Relations, 2025)
This thesis explores the relationship between strategic planning and institutional excellence in the context of the Lake Chad Research Institute. The study aims to develop a beginner's guide to understanding pathways for achieving institutional excellence through strategic planning. A mixed-methods approach was employed, combining qualitative and quantitative data collection and analysis methods. The study reveals that strategic planning is a critical factor in achieving institutional excellence, enabling organizations to adapt to changing environments, leverage opportunities, and mitigate threats. The findings highlight the importance of stakeholder engagement, leadership commitment, and continuous monitoring and evaluation in strategic planning. The study also identifies key pathways for achieving institutional excellence, including developing a clear vision and mission, setting objectives, and fostering a culture of innovation and learning. Based on these findings, the study develops a beginner's guide to strategic planning and institutional excellence, providing practical recommendations for policymakers, managers, and researchers in the Lake Chad Research Institute and similar organizations. The guide outlines steps for developing and implementing effective strategic plans, managing change, and promoting a culture of excellence. The study contributes to the existing literature on strategic planning and institutional excellence, offering insights and practical guidance for organizations seeking to improve their performance and impact.